2016
DOI: 10.1111/andr.12226
|View full text |Cite
|
Sign up to set email alerts
|

Does the number of veins ligated during varicococele surgery influence post-operative semen and hormone results?

Abstract: SUMMARYVaricocele is a well-established cause of male subfertility, which is directly proportional to its clinical grade. Although newer ultrasonic grading systems have taken into account the existence of pampiniform venous plexi, little is known about the clinical significance of the number of veins ligated during surgery. Very few undersized studies reported an influence which triggered the need to evaluate such association. This is a retrospective study of 378 patients who underwent left microsurgical subin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a cross sectional study of 1,162 patients, Majzoub et al [ 82 ] observed a positive correlation between the percentage of abnormal sperm heads and levels of ORP (p<0.001) and SDF (p<0.001). This confirms that OS is highly implicated in sperm DNA damage, especially SDF [ 83 84 85 ].…”
Section: Future Direction Of Oxidation-reduction Potential Clinical Umentioning
confidence: 99%
“…In a cross sectional study of 1,162 patients, Majzoub et al [ 82 ] observed a positive correlation between the percentage of abnormal sperm heads and levels of ORP (p<0.001) and SDF (p<0.001). This confirms that OS is highly implicated in sperm DNA damage, especially SDF [ 83 84 85 ].…”
Section: Future Direction Of Oxidation-reduction Potential Clinical Umentioning
confidence: 99%
“…Varicocelectomy was performed using the microsurgical subinguinal approach. All cases were done by the same urology team using a standardized approach [ 25 ]. Procedures were done under general anesthesia, utilizing a 2–3 cm subinguinal incision.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical varicocele repair improves semen parameters in NOA (Cakan & Altug, ; Kadioglu et al, ; Majzoub et al, ; Schlegel & Kaufmann, ; Tulloch, ), with varying rates of recovery of motile spermatozoa in the ejaculate (Weedin, Khera, & Lipshultz, ; Youssef, Abd‐Elaal, Gaballah, Elhanbly, & Eldosoky, ). Such improvements could result in spontaneous pregnancy.…”
Section: Introductionmentioning
confidence: 99%